Photodynamic inactivation of Candida albicans using bridged polysilsesquioxane films doped with porphyrin - Alvarez, María Gabriela (2012)
Novel photoactive bridged polysilsesquioxane films were prepared by doped with a porphyrin derivative. The films were formed by acid-catalyzed polycondensation reaction of a precursor of a bridged silsesquioxane, based on the reaction product of (glycidoxypropyl)trimethoxysilane with n-dodecylamine in the presence of 5-(4-carboxyphenyl)-10,15,20-tris(4-methylphenyl)porphyrin, followed by solvent evaporation. This procedure allowed obtaining flexible thin films. Absorption and fluorescence spectroscopic analysis showed the characteristic bands of the porphyrin in the visible region indicating that the photosensitizer is mainly embedded as monomer in the films. Photodynamic properties of the polymeric films were studied in solution containing photooxidizable substrates. Singlet molecular oxygen production was observed by the reaction with 9,10-dimethylanthracene and 9,10-anthracenediy l-bis(methylene)dimalonic acid in different media. Also, these films photosensitized the decomposition of L-tryptophan. In vitro investigations showed that these films produce photodynamic inactivation of Candida albicans cells in aqueous suspensions and on their surfaces. These films exhibit a photosensitizing activity causing a 2.5 log (99.7%) decrease of cellular survival after 60 min of irradiation with visible light. Also, the photocytotoxicity of the surfaces was tested under condition of microbial growth. Yeast cells exposed to the film and illuminated showed growth delay compared with controls. Studies of photodynamic action mechanism showed that the photoinactivation increased in D2O, while cells were protected in the presence of azide ion. In contrast, the addition of mannitol produced a negligible effect on the cellular phototoxicity. These results provide evidence that singlet oxigen produced by the polymeric film doped with porphyrin can successfully inactivate C. albicans in cell suspensions and deposited on the film surface.